2014
DOI: 10.7476/9788568334423
|View full text |Cite
|
Sign up to set email alerts
|

Os parasitas de ovinos

Abstract: Todo o conteúdo deste trabalho, exceto quando houver ressalva, é publicado sob a licença Creative Commons Atribição 4.0.Todo el contenido de esta obra, excepto donde se indique lo contrario, está bajo licencia de la licencia Creative Commons Reconocimento 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 162 publications
(281 reference statements)
3
34
0
21
Order By: Relevance
“…Analyses were carried out applying the F81+I+G model and 1000 bootstrap replicates for all analyses. Survey of vector-borne and nematode parasites in sheep from Southern Brazil lead animals to severe anemic conditions (Amarante, 2014), and thus, may explain the anemic status of the animals studied herein. The remainder eight anemic sheep also presented high values of EPG, ranging from 800 to 5,200.…”
Section: Discussionmentioning
confidence: 90%
“…Analyses were carried out applying the F81+I+G model and 1000 bootstrap replicates for all analyses. Survey of vector-borne and nematode parasites in sheep from Southern Brazil lead animals to severe anemic conditions (Amarante, 2014), and thus, may explain the anemic status of the animals studied herein. The remainder eight anemic sheep also presented high values of EPG, ranging from 800 to 5,200.…”
Section: Discussionmentioning
confidence: 90%
“…In the larval migration inhibition test (LMI), the 9.4 mg/mL concentration obtained 63.7% efficacy; a similar study carried out by Yoshihara et al (2014), who tested condensed tannins extracted from Acacia mearnsii, found that the 12.5 mg/mL concentration showed 56.3% inhibition, and only reaching 97.1% at the highest concentration used -100 mg/mL, thus demonstrating that better results can be obtained with a concentration increase. When analyzing the results of A. graveolens essential oil action in the different H. contortus development phases, L3 was found to be the most resistant, which can be attributed to the presence of the double cuticle at this larval stage as well as to the lower metabolic activity that occurs at this stage, a fact which was also mentioned by Amarante et al (2014).…”
Section: Discussionmentioning
confidence: 78%
“…After all these merozoites develop into microgametocyte or microgametocyte, and the microgamete will fertilize the macrogamete, creating a new oocyst non sporulated inside the intestinal cell. Occurring a cell rupture, the oocyst is released in the environment to infect a new host (AMARANTE et al, 2014).…”
Section: Eimeria Sppmentioning
confidence: 99%